(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines several problems in the formation and development of the digital economy, technological changes inherent in the digital economy, the impact of digital economy growth on global economic growth, the role of the digital economy in the global economy. It highlights the opportunities that digitalization, the shaping of the digital economy, create for consumers, the state, and society.